Determinación de zonas susceptibles a erosión hídrica en los cantones de Quilanga y Espíndola de la provincia de Loja, utilizando sistemas de información geográfica y teledetección - Palacios Merino, Leonardo Enrique (2016)
Soil erosion is a natural process, that has been accelerated as a result of the activities of humankind. This research was conducted in the cantons of Quilanga and Espíndola, where through the implementation of the Universal Loss Equation of the Revised Land (RUSLE) could identify susceptible to water erosion areas, using geographic information systems (GIS) and remote sensing as tools for manipulating the database generated through the collection of secondary data and field sampling. By manipulating the database, the information needed to get the data from each of the following factors R (index of rainfall erosivity), K (soil erodibility), LS (length and gradient generated slope), C (vegetation) and P (soil conservation practices), to finally generate the map of current soil erosion. This identified that 57,80 % (43 488,51 ha) of the total study area, have an erosion rate of 0-10 t/ha/year (Low), due to the presence of protected areas in the two counties that contribute the conservation of plant cover. While 28,33 % of the territory (21 314,39 ha) have an erosion rate of 50 to 200 t/ha/year (High) product of the irregular topography, cultivation in favor of the slope and the absence of soil conservation practices. The study area is located in the upper part of the sub Macará river basin, resulting in 11,28 % (20 519.36 ha) of its area it has a high susceptibility to be eroded, and 0,32 % (579.62 ha) have a very high susceptibility, while 28,79% have a susceptibility moderate to low. Taking into account the results different soil management practices as terracing, contour farming, strip including proposed.